Vom Kollektiv zum Individuum Transformationsprozesse am Übergang vom 4. zum 3. Jahrtausend v. Chr. in der Deutschen Mittelgebirgszone - Drummer, Clara (Scales of Transformation, 2022)
This book deals with the question of whether and how social identities changed in the German Lower Mountain Range at the end of the 3rd mill. BCE. It is stated that the transition from Late to Final Neolithic is accompanied by major changes in burial practices, possibly influenced by migration processes from the North Pontic steppe landscape. To answer the question of whether changes of social identities and burial practices were influenced by these migration processes, social group identities are reconstructed and analysed for transformational processes. Thus, this regional case study of the transition of the 3rd mill. BCE offers a social perspective on the archaeological changes as well as on findings from previous and recent aDNA studies. It becomes evident that the expression of group identities between the Late and Final Neolithic shifts from collective identities to the expression of individuals and their social roles. Possible reasons and triggers for this social transformation are considered alongside migration processes. The outcome is an interweaving of local practices and large-scale phenomena that were negotiated differently in local contexts. Depending on the scale, the networks demonstrate homogeneity over large parts of Central Europe or the diversity of local groups.